A cost-effectiveness analysis of glass ionomer cement as fissure sealant in school-based fissure sealant programme in the district of Pontian, Johor - Yacob, Habibah (2006)
Introduction: Community oral Health Care mainly focused on preventive measures such fluoridation, oral health promotion, oral cancer screening and school-based fissure sealant programme. To date, there has been no local evaluation of fissure sealant effectiveness especially in term of its cost. Objectives: To determine the status of occlusal surface of lower left FPM in sealed group and unsealed group after 5-year follow up, to determine the extra cost for sealed group, cost of complication and cost per averted occlusal caries for both groups and to compare the status of lower left permanent molar between sealed and unsealed groups. Methodology : This was a retrospective cohort study conducted in Pontian from June 2004 to October 2005. There were two phases in the study i.e. phase 1 for descriptive and cost analysis which involved 618 high caries risk group and phase 2 for questionnaire component which involved 322 high caries risk school children. Phase 1 only focused on dental treatment record (LP8) and financial data from administrative office and the data was collected from 1998 to 2003. For phase 2, subjects who were selected by a random sampling technique were given questionnaire for socio demographic status. Costing analysis was done based on the specified programme for the fissure-sealant preventive measure only. Results: The total retention rate of glass ionomer cement as fissure sealant in this study was 19.4°/o and the total loss was 80.6°/o. The status of sound occlusal lower left FPM in the sealed group was 88.4°/o and in the unsealed group was 76.8°/o. There was 11.6% of sealed teeth and 23.3°/o of unsealed teeth which developed caries after a 5-year follow up. For cost analysis, the extra cost for the sealed group was RM 1 ,294. 73, cost complication for the sealed group was RM 988.83, cost complication for the unsealed group was RM 1,927.10 and lastly cost per averted occlusal caries in the sealed group was RM 8.37 (95°/oCI 8.03,8. 72) and cost per averted occlusal caries in the unsealed was RM 8.35 (7.98,8. 72). Significant association was found between the status of occlusal lower left FPM and sealed/unsealed group while other associated factors being controlled at both univariable (crude OR=1.78; 95°/oCI 1.02,3.07) and multivariable analyses (OR=1.91; 95o/o Cl 1.05,3.49). Conclusion: The retention rate of GIC in this study was low. Occlusal status of lower left first permanent molar in those with fissure sealant have better caries prevention. The unsealed group has higher chances to develop caries. Considering the health gain (reduced caries) and the benefit enjoyed by those receiving fissure sealant, it is concluded that this fissure sealant programme is cost-effective even though the total calculated cost is slightly higher than that in unsealed group.